Design of a low-cost gas accumulation chamber for general purpose environmental monitoring - Domenico Longo; Serena Guarrera; Delia Ventura; Emanuele Cerruto; Salvatore Roberto Maugeri; Gaetano Giudice (Smart Agricultural Technology)
The need for accurate measurement of CO2 emissions from surfaces arises from various fields, particularly in precision agriculture, irrigation water management, wastewater management, volcanology, geothermal exploration, environmental and climate monitoring. This study introduces a novel, cost-effective closed dynamic accumulation chamber system designed to measure CO2 fluxes from soil and water surfaces. A short review of existing measurements techniques is provided, alongside a detailed explanation of key algorithms used for processing field data. The proposed system collects raw CO2 concentration data via an internal data logger. A custom-developed software suite enables real-time first-approximation flux calculation through a user-friendly Javascript web application compatible with smartphones with any type of operating system and web browser. A freely available Matlab® tool allows for post-processing data analysis for a more accurate flux calculation. After calibration against the commercial PP Systems EGM-5, assumed as a reference, some case studies in agriculture, wastewater treatment and volcanic environments demonstrate the instrument's versatility, showcasing its potential for advance in agricultural field and environmental sustainability.